Repensando la formación de docentes: oportunidades y desafíos - Sonia Abarca-Mora (Revista Electrónica Educare)
From the standpoint of a renovated vision that conceives teacher preparation as a continuing process, the author proposes a series of postulates of particular interest to professors and researchers working in colleges of education. These postulates define parents and students as persons, who having a generic social, familiar and cultural identity, act with full awareness of their abilities, limitations, tasks and responsibilities. They are people who are able to learn about multiple ways to have access to the most sophisticated technological and scientific developments. Herein lies the notion of an educator, permanently updated in his or her field of study, capable of conceiving, proposing and implementing epistemological, curricular, and methodological changes and breakthroughs. In shore, an academic immersed in a university tha is a laboratory for the conception and development of thoughtand action.